PROFIL SITOLOGI EFUSI PLEURA MALIGNA DI RSUD DR SOEDONO MADIUN PERIODE TAHUN 2021-2023 - Setiawan, Budi; Maulani, Yulita (LPPI Yayasan Almahmudi bin Dahlan, 2024)
Pleural effusion is a common symptom resulting from various diseases, and malignant pleural effusion occurs when cancer cells are present in the fluid. Determining the cause can be challenging due to the wide range of potential primary tumors. Cytological analysis is essential for diagnosing pleural effusion. This study aimed to identify the cytological profile of malignant pleural effusion at Dr. Soedono General Hospital, Madiun, from 2021 to 2023. It used a retrospective descriptive design, analyzing medical records of patients diagnosed with malignant pleural effusion during this period. Data was sourced from the hospital's Laboratory Information Systems program, and descriptive frequency analysis was applied. The results showed that out of 158 patients diagnosed with pleural effusion, 147 (93.04%) had non-neoplastic effusion, and 11 (6.96%) had neoplastic effusion. Among the neoplastic cases, 8 (5.06%) were confirmed as malignant pleural effusion, with adenocarcinoma being the most common cause, identified in 5 patients (62.50%).